Antimicrobial drug resistance of enteric bacteria from broilers fed antimicrobial growth enhancers and exposed poultry abattoir workers - Picard, J.A. (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2007.